Implementasi Kegiatan Ekstrakurikuler Seni Kaligrafi dalam Mengembangkan Spatial Intellegence - Nada, Muhammad Yusrun; Kinesti, Rakanita Dyah Ayu (ALSYS, 2024)
The purpose of this research is to examine the implementation of the calligraphy extracurricular activity at MI Khurriyatul Fikri Pasuruhan Lor Kudus. This study employs a descriptive qualitative research approach, and, in line with the object of study, it is a field research. The focus is on the application of spiritual and tafakkur methods in the learning process. The subjects of the research are the students participating in the calligraphy extracurricular activity and the guiding teachers involved in the program. The first step in this research is to identify the role of spiritual and tafakkur methods in the calligraphy learning process. Subsequently, field observations are conducted to directly observe the implementation of these methods, along with interviews with teachers and students to explore their perceptions of the impact of the spiritual and tafakkur methods on the creative process and character development of the students. The data collected is analyzed descriptively, focusing on the impact of both methods on students' visual-spatial intelligence, emotional intelligence, and religious character development. The research results indicate that the spiritual method applied in the calligraphy extracurricular activity helps students to perceive each artwork as a form of worship and an expression of love for Islamic teachings. Meanwhile, the tafakkur method encourages students to think deeply and reflectively, so they not only focus on the aesthetics of the artwork but also understand the religious and philosophical values embedded within. The conclusion of this research is that the implementation of spiritual and tafakkur methods in the calligraphy extracurricular activity has a positive impact on the development of students' religious character, emotional intelligence, and reflective abilities. Furthermore, this method also proves to enhance students' visual-spatial intelligence, in line with the basic principles of calligraphy art, which demand precision and deep contemplation. This study recommends that similar approaches be more widely implemented in other Islamic educational institutions to integrate art education with the spiritual development of students.